Do the Informatics Freshmen Satisfied with Information Technology-assisted Learning? A Study During the Pandemic Era - Daniel Febrian Sengkey; Feisy Diane Kambey; Pinrolinvic Duadelfri Kurnialimki Manembu; Heilbert Armando Mapaly; Kenneth Yosua Rumawas Palilingan; Arthur Morits Rumagit; Salvius Paulus Lengkong; Rizal Sengkey; Angelina Stevany Regina Masengi (Jurnal Teknik Informatika, 2022)
Over three years after Patient 0 was identified, COVID-19 is still a scourge for the world. It has taken its toll in various aspects, including altering human day-to-day routines. Its impact on education forces classes to be held online in a synchronous virtual meeting or through asynchronous learning that utilizes a Learning Management System (LMS). This study addressed the satisfaction issue of freshmen, who just entered college and must be facing online learning held through an LMS.